2017
DOI: 10.7860/jcdr/2017/28296.10417
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Vaginal Flora and Incidence of Asymptomatic Vaginosis among Healthy Women and in Women with Infertility Problems of Reproductive Age

Abstract: Introduction: The normal vaginal flora is highly complex, dominated by lactobacilli of doderlein that plays a vital role in maintaining the women's health and inhibits other pathogenic microorganisms. Fluctuation in local environment or exposure to any exogenous and endogenous sources changes the vaginal flora over a period of time. Disruption of the vaginal ecosystem changes the microflora of the healthy vagina, altering the pH and predisposing to lower reproductive tract infections. The change in the microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 41 publications
0
53
0
2
Order By: Relevance
“…(10) Studies have shown that the presence of certain Lactobacillus species during ART procedures may have a positive impact on outcome (4,11,12), whereas bacterial vaginosis is associated with poorer results. (13,14) The use of the vaginal microbiome as a predictor for ART outcome has not yet been investigated. We aimed to answer the following questions: First, is the presence or absence of certain vaginal bacteria associated with failure or success to become pregnant after an IVF or IVF-ICSI treatment?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) Studies have shown that the presence of certain Lactobacillus species during ART procedures may have a positive impact on outcome (4,11,12), whereas bacterial vaginosis is associated with poorer results. (13,14) The use of the vaginal microbiome as a predictor for ART outcome has not yet been investigated. We aimed to answer the following questions: First, is the presence or absence of certain vaginal bacteria associated with failure or success to become pregnant after an IVF or IVF-ICSI treatment?…”
Section: Introductionmentioning
confidence: 99%
“…(8) Propionibacteriumand Actinomyces were also found to impair clinical outcomes (17). Bacterial vaginosis was further associated with infertility and early spontaneous abortion (13,14).…”
mentioning
confidence: 99%
“…In a study conducted by Singaravelu, et al over a period of 6 months in 116 women with infertility problems at Sri Lakshmi Narayana Medical College and Hospital Pondicherry, it was observed that women with infertility problems showed abundance of Bacterial Vaginosis (Lactobacillus, 3.5%) compared to healthy women (Lactobacillus, 27.8%). Author of the study recommended the screening of vaginal flora as a routine for all women, especially in women undergoing infertility treatment [9]. In another study conducted by Pramanik, et al in 510 women with manifestations such as infertility, it was found that BV infection is associated with infertility and its absence leads to pregnancy, emphasizing its screening and treatment [10].…”
Section: Prevalence and Association Of Bv With Infertilitymentioning
confidence: 99%
“…It most often causes leucorrhoea with a foul odour and sometimes irritations that lead women to seek gynaecological care [2]. It is associated with the risk of preterm birth, miscarriage, and low birth weight when presenting in pregnant women [3], as well as the risk of pelvic in ammatory diseases [4]. Bacterial vaginosis predisposes women to serious health problems, including the acquisition and transmission of various pathogens such as herpes simplex virus-2 [5], human immunode ciency virus-1 [6], papillomavirus [7], Neisseria gonorrhoeae, Trichomonas vaginalis, and Chlamydia trachomatis [8,9].…”
Section: Introductionmentioning
confidence: 99%